2021
DOI: 10.1186/s12985-021-01686-x
|View full text |Cite
|
Sign up to set email alerts
|

High throughput sequencing of whole transcriptome and construct of ceRNA regulatory network in RD cells infected with enterovirus D68

Abstract: Background With the advancement of sequencing technologies, a plethora of noncoding RNA (ncRNA) species have been widely discovered, including microRNAs (miRNAs), circular RNAs (circRNAs), and long ncRNAs (lncRNAs). However, the mechanism of these non-coding RNAs in diseases caused by enterovirus d68 (EV-D68) remains unclear. The goal of this research was to identify significantly altered circRNAs, lncRNAs, miRNAs, and mRNAs pathways in RD cells infected with EV-D68, analyze their target relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Their relative propensity for binding to diverse interaction complexes, for instance, contributes to the diversity of this activation ( O’Donnell et al, 2012 ). Importantly, it has been demonstrated that c-Fos is a target gene for miR-150-5p ( Wang et al, 2021 ), which was consistent with our previous findings ( Si et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Their relative propensity for binding to diverse interaction complexes, for instance, contributes to the diversity of this activation ( O’Donnell et al, 2012 ). Importantly, it has been demonstrated that c-Fos is a target gene for miR-150-5p ( Wang et al, 2021 ), which was consistent with our previous findings ( Si et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Bowtie2 (v2.2.5) was used to align clean reads to the gene set, a database generated by the Beijing Genome Institute (BGI) in Shenzhen that includes known and new, coding and non-coding transcripts, and then RSEM (v1.2.12) was utilized to calculate gene expression levels. The original sequencing data used in the article, and the original data processing are all consistent with the source of the published articles in our laboratory (Si et al, 2021).…”
Section: Rna Extraction and Lncrna Sequencingmentioning
confidence: 72%
See 1 more Smart Citation